Integration of Islamic Values in Stunting Prevention Management at Rural Islamic Educational Institutions: A Case Study at Madrasah Ibtidaiyah (MI) in Nganjuk Region - Akhmat Fanani Ridho (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2025)
Stunting persists as a critical public health challenge in rural Indonesia, demanding contextually relevant interventions. Recognizing the influential role of local institutions, this qualitative case study investigates the potential of rural Islamic educational institutions (Madrasah Ibtidaiyah - MI) in Nganjuk Region to integrate religious values into stunting prevention management. The research specifically aimed to analyze how Islamic values are incorporated within stunting prevention efforts at these MIs. Data was gathered through in-depth interviews with teachers, parents, and health workers, alongside observations and document analysis across five MIs. Key findings reveal that Islamic principles, such as the emphasis on balanced nutrition grounded in Islamic dietary ethics and hygiene practices linked to the concept of thaharah (ritual purity), significantly strengthen program acceptance and implementation. Framing health messages through these shared values enhanced cultural resonance and community engagement. However, significant challenges hinder optimal integration, including resource limitations (funding, materials, trained personnel) and gaps in parental awareness regarding stunting and optimal childcare practices. The study concludes that strategically integrating Islamic values offers a powerful, culturally sensitive approach to stunting prevention management within rural MI settings. Recommendations include formally embedding relevant health and nutrition concepts within the MI curriculum, fostering robust collaboration between educational institutions, health services, and religious leaders, and implementing targeted initiatives to increase parental knowledge and resource allocation to overcome existing barriers. This integration leverages existing trust and faith structures for more effective health outcomes.